Research recommendations to better understand the potential health impacts of microplastics to humans and aquatic ecosystems - Thornton Hampton, Leah M.; Bouwmeester, Hans; Brander, Susanne M.; Coffin, Scott; Cole, Matthew; Hermabessiere, Ludovic; Mehinto, Alvine C.; Miller, Ezra; Rochman, Chelsea M.; Weisberg, Stephen B. (Microplastics and nanoplastics, 2022)
To assess the potential risk of microplastic exposure to humans and aquatic ecosystems, reliable toxicity data is needed. This includes a more complete foundational understanding of microplastic toxicity and better characterization of the hazards they may present. To expand this understanding, an international group of experts was convened in 2020–2021 to identify critical thresholds at which microplastics found in drinking and ambient waters present a health risk to humans and aquatic organisms. However, their findings were limited by notable data gaps in the literature. Here, we identify those shortcomings and describe four categories of research recommendations needed to address them: 1) adequate particle characterization and selection for toxicity testing; 2) appropriate experimental study designs that allow for the derivation of dose-response curves; 3) establishment of adverse outcome pathways for microplastics; and 4) a clearer understanding of microplastic exposure, particularly for human health. By addressing these four data gaps, researchers will gain a better understanding of the key drivers of microplastic toxicity and the concentrations at which adverse effects may occur, allowing a better understanding of the potential risk that microplastics exposure might pose to human and aquatic ecosystems.